Does good financial behavior reduce the negative impact of financial fragility on individuals’ financial optimism? The never-ending Lebanese crisis case - Mawad, Jeanne Laure (International Journal of Innovative Research and Scientific Studies, 2023)
This study examines the negative link between financial optimism and financial fragility in a time of a severe crisis, focusing on the positive impact of good financial behavior on this relationship, while also taking into consideration demographic factors. A comprehensive survey of 328 participants, data were collected during the 2019–2021 Lebanese crisis, and a logistic regression analysis was used to verify the hypothesis. This study is the first of its kind in Lebanon and the Middle East and sheds light on the undertreated subject of financial optimism, fragility, and behavior among the Lebanese population. The results of the study show that financial fragility has a negative impact on individuals' financial optimism, but that good financial practices can mitigate this relationship. Financial optimism is affected by individuals’ income level but is not affected by other demographic factors such as gender, marital status, education levels, and the number of financial dependents; good financial behavior is found to increase financial optimism among Lebanese individuals, regardless of demographic factors. The findings have significant policy implications, indicating the need for policymakers to prioritize promoting positive financial behavior and integrating financial education into school curricula.